Effects of different training programs on throwing velocity in handball: Review - Markovic, S.; Markovic, K. (XXI Scientific Conference "FIS COMMUNICATIONS 2018" in physical education, sport and recreation (Nis, Serbia, October 18-20, 2018), 2018)
Competitive success in handball depends of the numerous factors such as technical skills and tactics, the anthropometric characteristics, and highs levels of force, power, and throwing velocity. The aim of this study was to analyze previous research about training programs that effect on throwing velocity in team handball last ten years and to analyze which training program is the best for improving that one of the most important part of handball, throw. An extensive electronic database search was performed using MEDLINE, ERIC, PubMed, Google Scholar, SCInIdex and ScienceDirect to identify relevant articles that investigated the effects of various training programs on throwing velocity. Ten studies were analyzed in this review. A challenging aspect of sports training is to maximize training transfer to a complex motion of overarm throwing in team handball.